A Mobile travel application with itinerary planner for Kampar tourism - Low, Weng Liang (2023)
Malaysia stands as one of the largest tourists’ attractions in the world. In every year, there are many tourists around the globe will pay a visit and discover this magnificent nation. This is because Malaysia contains some of the attractive tourists’ attractions compared to other countries in the world. The majority of the tourists who pay a visit to Malaysia are mainly wanting to visit some of the magnificent historic landmarks as Malaysia is a country rich in history. There are still some of the tourists who would like to enjoy other activities such as discover incredible cities in Malaysia or eat wonderful Malaysian food. However, the development of tourism industry in small town area such as Kampar, Perak is very slow compared to the capital city of Malaysia, Kuala Lumpur. This is because the tourism industry in Malaysia is mainly focus on big cities which causes development of tourism industry in small town area is being ignored. Due to the development of tourism industry in small town area is being ignored, the information about the small-town area such as Kampar is very limited and hard to be found on the websites. Hence, the tourists may also ignore the travel plan to make a trip to Kampar as the information is limited on Internet and attractions shown is limited as well. So far, there is no mobile application developed by any company in Malaysia for Kampar tourism. In conclusion, a mobile travel application is necessary to be built so it could offer a complete travel guidance for the tourists when they make their trip to Kampar.